Ontogenetic and secondary sexual dimorphism variation in Platalina genovensium (Chiroptera: Phyllostomidae) - Ruelas, Dennisse (2019)
Ontogenetic development and sexual dimorphism in bats are aspects frequently studied; however, this information is not available for Platalina genovensium, a threatened bat species that occurs in dry ecosystems between Peru and Chile. In this study, I present the first information about the ontogeny and sexual dimorphism of the species based on the review of collection specimens. I analyzed 31 specimens including juveniles and adults to assess ontogeny. Sexual dimorphism was tested by statistical and multivariate analysis using one external and 14 cranio-dental variables on adults only. Descriptions of juvenile (age class I) and adult stages (age classes IV and V) are presented, as well as the skull of a fetus. I found that the forearm length did not present statistically supported differences between sexes, whereas at the cranial-dental level, the mandibular branch width was the main dimorphic variable. I suggest that the differences reported between juvenile and adult specimens and between females and males should be understood from the perspective of evolution and adaptation and not only ontogenetically.